The carbon credit conundrum: Which analytical method should be used for determining soil organic carbon content in South Africa? - Cloete, Willie Herman; du Preez, Gerhard; Van Zijl, George Munnik (Geoderma Regional, 2025)
Accurate quantification of soil organic carbon (SOC) content is essential for the assessment of carbon credits. In South Africa, the standard methodologies for carbon credit assessment does not specify which analytical method should be used for determining SOC content. The study aimed to determine which analytical method should be used for determining SOC content for the assessment of carbon credits. Secondly, it determined whether pedotransfer functions could be used for transferring SOC content values between methods. Two-hundred-and-twenty topsoil (0–30 cm) samples were collected and analysed for SOC content with the three analytical methods: Walkley-Black wet-oxidation (WB), total dry combustion (TDC) and loss-on-ignition (LOI). The study found that the TDC method should still be considered the preferred method for determining SOC content for the assessment of carbon credits in South Africa. The WB method should be avoided if a soil is expected to have a high SOC content, while the LOI method could still be used for determining SOM, however, this method should be avoided when determining SOC content. The study also reached the second aim by successfully creating pedotransfer functions between all three methods. However, only the WB and TDC methods had a very strong relationship (R2 = 0.91) and showed that accuracy start to decrease significantly after 2.5 % SOC content. Therefore, the pedotransfer function (SOCWB = −0.157 + 0.895 x SOCTDC – 0.0149 x SOCTDC2–0.000606 x SOCTDC3) could be used for transferring SOC content values with SOC content up to 2.5 %.